A perfectly competitive economy is an economy without welfare relevant endogenous learning - Karine Nyborg (University of Oslo, Department of Economics, 2021)
I demonstrate a straightforward but apparently widely unrecognized implication of the standard requirements for perfect competition: an economy in which consumers can choose to learn is generally not perfectly competitive. In particular, if endogenous welfare relevant learning is feasible, the economy cannot be perfectly competitive unless identical learning choices by all consumers are guaranteed. If the new information is not shared with everyone, asymmetric information arise; if information is shared, externalities arise. The standard conditions for the two fundamental welfare theorems, thus, implicitly preclude heterogeneous welfare relevant learning decisions.
Keywords: D41; D50; D60; D61; D62; D82; 330; Perfect competition; fundamental welfare theorems; learning; symmetric information; externalities